Netherton Syndrome in Children: Management and Future Perspectives - Barbati, Federica; Giovannini, Mattia; Oranges, Teresa; Lodi, Lorenzo; Barni, Simona; Novembre, Elio; Baldo, Ermanno; Cristofolini, Mario; Stagi, Stefano; Ricci, Silvia; Mori, Francesca; Filippeschi, Cesare; et al. (Frontiers in Pediatrics, 2021)
Netherton syndrome (NS) is a genetic, multisystemic disease classically distinguished by a triad of clinical manifestations: congenital ichthyosiform erythroderma, hair shaft abnormalities, and immune dysregulation. Due to the complex pathogenesis of the disease, there are no specific therapies currently accessible for patients with NS. An early diagnosis is crucial to start the correct management of these patients. A multidisciplinary approach, including specialists in immunology, allergology, and dermatology, is necessary to set up the best therapeutic pathway. We conducted a review with the aim to summarize the different therapeutic strategies currently available and potentially available in the future for children with NS. In conclusion, this article offers practical suggestions for the management of patients with NS based on a literature review. Further comprehension of the pathophysiology of the disease could lead to more efficacious specific therapeutic options, which could allow a change in the natural history of the NS.